Plasma endothelin-1 and cardiovascular risk among young and healthy adults. Issue 1 (March 2015) - Bossard, Matthias; Pumpol, Katrin; van der Lely, Stéphanie; Aeschbacher, Stefanie; Schoen, Tobias; Krisai, Philipp; Lam, Tschuenschen; Todd, John; Estis, Joel; Risch, Martin; Risch, Lorenz; Conen, David
Abstract: Objectives: Endothelial dysfunction is a major precursor of atherosclerosis. The aim of this study was to assess the interrelationships between plasma endothelin-1 (ET-1) levels and cardiovascular risk among young and healthy individuals. Methods: We performed a population-based study among 2160 healthy adults aged between 25 and 41 years in the Principality of Liechtenstein. Individuals with prevalent cardiovascular disease, diabetes or a body mass index >35 kg/m 2 were excluded. Plasma ET-1 was measured using a novel high-sensitive, single-molecule counting technology. The relationships between plasma levels of ET-1 and various cardiovascular risk factors were assessed by multivariable regression analyses. Results: Median age of our population was 37 years. Median ET-1 levels across ET-1 quartiles were 1.86, 2.33, 2.76 and 3.48 pg/mL. After multivariable adjustment, there were significant correlations of ET-1 with systolic blood pressure (β per 1-unit increase in log transformed ET-1 2.30 (95% confidence interval (CI) 1.03; 3.58, p = 0.0004), C-reactive protein (β 0.19 (95% CI 0.03; 0.34, p = 0.021), glomerular filtration rate (β −1.73 (95% CI −3.17; −0.29, p = 0.019), and current smoking (Odds ratio 1.94 (95% CI 1.39; 2.71, p < 0.0001). We also found a highly significant association between ET-1 levels and overall cardiovascular risk estimated by the "Prospective Cardiovascular Münster" (PROCAM) and the Framingham score (β 0.18 (95% CI 0.06; 0.31, p = 0.004, and β 0.11 (95% CI 0.05; 0.16), p < 0.0001, respectively). Conclusions: Plasma ET-1 levels are easily measurable in healthy adults and correlate with major cardiovascular risk factors and global cardiovascular risk. Highlights: Novel assays simplify the determination of the plasma endothelin-1 (ET-1) levels. Plasma ET-1 levels were quantified in a large cohort of young and healthy adults. ET-1 levels are independently associated with an individual's global cardiovascular risk. Further, systolic blood pressure seems strongly linked to plasma ET-1 levels. ET-1 also correlates with current smoking, glomerular filtration rate and inflammation.